2015
DOI: 10.1596/978-1-4648-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Services in Trade: A Toolkit for Competitiveness Diagnostics

Abstract: Some rights reserved 1 2 3 4 17 16 15 14 This work is a product of the staff of The World Bank with external contributions. The fi ndings, interpretations, and conclusions expressed in this work do not necessarily refl ect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this work do not imply any judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…In this context, our results suggest that probably the easiest way for maintaining the effect of the evolution of the productive structure is by introducing services whose set of required capabilities is similar, but a little more complex; for instance, developing intangible assets such as patents requires the presence of sophisticated machineries and an additional input of capabilities. It is worth noting that our argument is in accordance with the conclusions in [18] where it was indicated that services tend to grow in importance for the economy as the level of a country’s development rises.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, our results suggest that probably the easiest way for maintaining the effect of the evolution of the productive structure is by introducing services whose set of required capabilities is similar, but a little more complex; for instance, developing intangible assets such as patents requires the presence of sophisticated machineries and an additional input of capabilities. It is worth noting that our argument is in accordance with the conclusions in [18] where it was indicated that services tend to grow in importance for the economy as the level of a country’s development rises.…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, since the nature of the trade in services makes it difficult to collect service data as accurately as goods data, it includes data mainly on two out of the four modes of trade in services; cross-border trade flows and consumption abroad. A detailed description of the construction of the dataset is provided in Appendix B of [18]. …”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies and reports have analysed the role of services trade and related policies from an economic development perspective (see for instance Mattoo and Payton 2007;Cali et al 2008;World Bank 2010;Saez et al 2015;Dihel and Goswami 2016;Balchin et al 2016), complementing studies of developed economies (e.g. Breinlich and Criscuolo 2011;Wagner 2012).…”
Section: Services Trade and Structural Transformationmentioning
confidence: 99%
“…Of course, more than an open trade regime and good economic governance will be needed to support competitive local services sectors and generate positive productivity effects. Services are relatively intensive in human capital, so it is important to have sufficiently high-quality educational services at primary, secondary, and, as it becomes appropriate, tertiary level (Saez et al 2015) so as to ensure that workers have the skills demanded by service suppliers in areas such as ICT, finance, and business and professional services (Dihel et al 2010). A supportive regulatory regime is also important, which, as discussed below, calls for mechanisms to allow for interactions with services firms and users of services (Dihel and Goswami 2016).…”
Section: The Relationship Between Institutional Quality and Stris Is mentioning
confidence: 99%
See 1 more Smart Citation